Mostra de astronomia: um instrumento de divulgação científica e tecnológica na educação básica - Silva, Edgar Gomes da (2023)
The offer of experimental activities concomitant with theoretical content motivates students and facilitates the teaching-learning process. Participation is enriched when the experimental experience is combined with the content studied. Conversely, when carrying out an experiment, the student is motivated to acquire theoretical knowledge that explains the observed phenomena. Science Fairs, as the theme of this dissertation, they fit into this perspective and represent true peda- gogical spaces for multiple learning, stimulating and providing the student with an immersion in investigative, scientific and technological activities, which go beyond the perspectives expected only in textbooks. They can and should be seen as a conceptual vehicle for transformation in the classroom classroom, taking current Science teaching, bookish and based on the act of memorizing, to another level of pedagogical practice. Therefore, understanding Science Fairs as spaces for social interaction, cooperation and challenges that facilitate the evolution of spontaneous conceptions about Science and the formation of scientific concepts, the Educational Technical Product (PTE) linked to this work was an online page (site)2, with the results that were obtained during the holding of an Astronomy Exhibition at the Luis Eduardo Magalhães State School, with 9 1st grade classes of the new regular high school, located in the city of Tucano-BA. With this, it was possible to ob- serve that it is a pedagogical activity that it enabled students to exercise scientific research, preparing and interpreting texts for public presentation, orality, posture, creativity, among others, as are consistent with the skills and abilities reiterated by BNCC. This is a successful and interdisciplinary contextualized activity.